Dementia-friendly Community Case Studies across Europe. - (:unkn) unknown (My University, 2015)
"Dementia-friendly communities" are a growing phenomenon across Europe and other parts of the world. The numbers of people with dementia continues to increase, mainly because of increased life expectancy and growing numbers of older people. There are many different types of dementia (Alzheimer's disease is the most common) but they are all brain diseases affecting a person's memory, perception, understanding, orientation, and communication. There is currently no cure or universally effective treatment for the condition and the concept of "dementia-friendly communities" has developed as a collective approach to enable people with dementia to live as well as possible with the condition. This collection of case studies or so called "mapping paper", has been produced as a way of sharing information about "dementia-friendly community" activities across Europe. It has been commissioned by the European Foundations Initiative on Dementia (EFID) and produced by a UK non-governmental organisation, the Mental Health Foundation. The aim of the paper is to map what it is commonly referred to as "dementia-friendly community" work and inspire people to develop "dementia-friendly community" activities in their own local areas, or within their area of particular knowledge or expertise, policy or practice. The contents of the paper have been informed by an online survey, telephone interviews and literature review across Europe that were commissioned by EFID and undertaken by the Mental Health Foundation between May 2014 and May 2015.
Keywords: Gesundheitswesen; Gesundheit; Krankheit; Gemeinde; Sozialeinrichtung; Gesundheitseinrichtung; Fallstudie; Gesundheitszustand; Gesundheitsversorgung; Demenz; Alzheimer; Bürgerbeteiligung; Gesundheitsberichterstattung; Kommunale Gesundheitspolitik; Altenpflege; Internationaler Vergleich